Recent Advancements in Sensor Technologies for Healthcare and Biomedical Applications - Wenfeng Zheng; Yichao Yang; Chao Liu; Wenshuo Zhou (Sensors)
Biomedical sensors are the key units of medical and healthcare systems [...]